Incorporating Satellite Data Into Weather Index Insurance - Black, Emily; Greatrex, Helen; Young, Matthew; Maidment, Ross I. (American Meteorological Society, 2016)
What: Twenty-three people from six countries came together to discuss how drought insurance based on remotely sensed data can reduce the impact of weather shocks on some of the poorest people in the world. Participants were drawn from financial and agricultural sectors, nongovernmental and governmental organizations, and universities.